Reuse of sewage treatment plant effluent and domestic wastewater as a sustainable alternative water supply for landscape irrigation using drip irrigation system - Halimatul Syahida, Mohamad Sanusi (2012)
The main purpose of this study was to reuse of sewage treatment plants effluent and domestic wastewater as a sustainable water supply to landscape irrigation using drip irrigation. Generally, reuse of freshwater consumption is devoted to agricultural activities that caused critical water demand. Wastewater reuse can provide an alternative solution to these problems by supplying the water and nutrients needed for landscape irrigation. Nitrogen, phosphorus and potassium are the major, nutrients for plant growth, thus, the sewage treatment plants effluent and domestic wastewater are sustainable to be used as an alternative water supply for landscape irrigation as all of these nutrients can also be found in these two alternatives. However, the safe use of wastewater for irrigation purpose should be determined. Therefore, a test was done in environmental laboratory in order to test the water quality of sewage treatment plant effluent, domestic wastewater and tap water. Besides, this study also was done to determine the effectiveness of using these types of wastewater in contributing in the plant growth. In an effort to test it effectiveness, the wastewater was irrigated to three gardens which were planted with the same types of plant in the same quantity where garden A was irrigated with tap water, garden B irrigated with domestic wastewater while garden C was irrigated with sewage treatment plant effluent. The plants used in this study are 'Corrilair Yellow', 'Ixora', 'Licuala Grandis', Loropetalum' and 'Spider Lily' which are measured based on their overall height, canopy opening, leaves size and leaves height. The drip irrigation was used to irrigate the water supply to each garden as it is the most effective way to reduce water consumption and the pollutants that will be produced. Sewage treatment plants, domestic wastewater and tap water are safe to be used for landscape irrigation based on the results shown by the growths of the plant. Moreover, all the plants that were planted in garden C shown a more blooming growth compared to garden A and garden B.